(untitled) (Palestine Issues on Indonesian Society, 2025)
This paper explores the intersection of Islamic philanthropy and political Islam in fundraising efforts for Palestine in Indonesian society. It investigates the role of Islamic charitable organizations and religious institutions in mobilizing financial and material resources to support Palestinian causes, with a focus on the growing trend of political Islam influencing charitable initiatives. Using case studies of major Indonesian Islamic organizations, such as Muhammadiyah and Nahdlatul Ulama, the paper analyzes how they leverage both religious duty and political ideology to advocate for Palestine. The research examines the motivations behind these fundraising campaigns, the types of resources mobilized, and the impact of these efforts on Indonesian public opinion and foreign policy. The study also delves into the broader political implications of this form of philanthropy, arguing that Islamic charitable actions for Palestine are increasingly intertwined with political Islam, which advocates for solidarity with oppressed Muslim populations globally. The paper contributes to understanding how political and religious movements in Indonesia use philanthropy not only as a tool for humanitarian aid but also as a vehicle for political activism in support of Palestine.